Learning to innovate: Students and teachers constructing collective innovation practices in a primary school’s makerspace - Leskinen, Jasmiina; Kajamaa, Anu; Kumpulainen, Kristiina (Frontiers in Education, 2023)
The need to foster citizens’ innovation skills is widely recognized. Although current research acknowledges the potential of makerspaces to promote innovation activities, research still lacks an understanding of underlying mechanisms that can lead the creation of innovations in makerspaces by students. Moreover, research to date has overlooked how innovation practices are formed in K-12 makerspaces. In this sociocultural study, we used ethnographic video data from a Finnish primary school’s makerspace and applied methods of abductive Video Data Analysis to investigate how innovation practices are constructed in first to sixth grade students’ and teachers’ interactions. The results of this study show that the innovations created by the students in the makerspace were an outcome of students’ and teachers’ collective innovation practices. The study provides a typology of these collective innovation practices, namely: taking joint action to innovate, navigating a network of resources, and sustaining innovation activities. Further, our results reveal that the collective actions encouraged students to use skills deemed to be important for innovation creation. Also, adding to existing research knowledge, our results reveal two mechanisms that potentially promote students’ learning to innovate. These mechanisms include the teachers’ orientation to facilitating open-ended STEAM projects and practices that emphasize students’ ownership over their personal projects.